A case of myocardial muscular bridging causing severe hypotension during exercise-electrocardiography test - Gamze Babur Güler; Hacı Murat Güneş; Ekrem Güler; Tamer Atasever; Ali Metin Esen (KARE Publishing, 2016)
Outlining the severity of the myocardial bridge (MB) is a critical step for selecting the appropriate option among medical, surgical, or angioplasty-based treatments. Invasive treatments are usually preferred if treatment-resistant symptoms are observed or ischemia is proven by tests such as fractional flow reserve or myocardial perfusion scintigraphy (MPS). In this report, we present a patient who developed severe hypotension during treadmill exercise test, even though there were no perfusion defects during adenosine-induced MPS. This case suggests MPS with adenosine is not a good choice for evaluating ischemi